Role of diffuse endocrine system and cellular homeostasis of epithelial cells of the stomach mucosa in development and progression of peptic ulcer of the duodenum (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
Aim of investigation. To determine new pathogenic mechanisms of peptic ulcer of the duodenum (PUD) associated to Helicobacter pylori, basing on features of diffuse endocrine system (DES) and processes of cellular homeostasis of stomach mucosa (SM) epithelial cells, to improve quality of PUD remission achievement.Material and methods. Overall 115 patients were investigated: 100 – with PUD associated with H. pylori infection and 15 – generally healthy persons. Patients with PUD were separated into two peer groups: in the first group eradication H. pylori under traditional 7-day’s algorithm with application of omeprazole 20 mg bid, clarithromycin 500 mg bid and amoxicillin 1000 mg bid was carried out, in the second group melaxen (melatonin) 3 mg per day was added to the traditional mode of eradication. Then the first group continued to receive omeprazole, the second – omeprazole in combination to melaxen up to complete healing of ulcerative defect. Both groups of patients with PUD were investigated dynamicly, prior onset of treatment and after six weeks under the common program including clinical methods of investigation, gastroduodenoscopy (GDS), general morphological, immunohistochemical studies and histiobacterioscopy. The GDS-control was carried out in two, with four and six weeks. The group of generally healthy persons was investigated once by similar procedure.Results. The relapse of PUD is associates with hyperplasia of epithelial cells of the stomach, immunopositive to nitric oxide synthase, endothelin-1, melatonin, and with subsequent increase in number of epithelial cells, immunopositive to Ki-67, and increase of apoptotic activity. Eradication of H. pylori in patients with PUD reduces proliferation of epithelial cells of the SM and in the greater degree – their apoptotic activity that promotes healing of ulcerative defect. Introduction to the algorithm of eradication treatment of melaxen significantly increases the rate of elimination H. pylori, reduces terms of healing of duodenal ulcers. At application of melaxen and omeprazole in PUD maintenance treatment parameters of DES and cellular homeostasis of epithelial cells of the SM recovered in significantly greater degree, than at single omeprazole treatment.Conclusions. Addition of melaxen in the algorithm of eradication treatment increases rate of H. pylori elimination, reduces terms ulcer healing, improves parameters of DES and epithelial cells homeostasis of the SM.